2020
DOI: 10.22201/fmvz.24486760e.2020.3.925
|View full text |Cite
|
Sign up to set email alerts
|

Reacciones adversas de los fármacos en los equinos

Abstract: Artículo originalmente publicado en:Sumano López H, Lizárraga Madrigal I, Ocampo Camberos L, Obregón Jurgens K. Reacciones adversas de los fármacos en los equinos. Veterinaria México. 2000;31(4):329–54.- - - El conocimiento de las reacciones adversas a los fármacos (RAF), identificadas recientemente o ya conocidas de antemano, limita necesariamente la ocurrencia de iatrogenias y facilita la pronta recuperación de los pacientes equinos. Las RAF pueden ocurrir en cualquier momento y bajo una gran variedad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 110 publications
0
6
0
Order By: Relevance
“…Conversely, eggs in contact with 0.1 mg/mL thiabendazole showed a more intense green fluorescent colouration without presenting orange or red dying (Figures 3 G–I), and also a 1 st stage larvae were stained with green fluorescent dye in the same way. That could be explained by the mechanism of action of benzimidazole that does not affect the cuticles or cell membranes of the nematodes [52,53] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, eggs in contact with 0.1 mg/mL thiabendazole showed a more intense green fluorescent colouration without presenting orange or red dying (Figures 3 G–I), and also a 1 st stage larvae were stained with green fluorescent dye in the same way. That could be explained by the mechanism of action of benzimidazole that does not affect the cuticles or cell membranes of the nematodes [52,53] …”
Section: Resultsmentioning
confidence: 99%
“…That could be explained by the mechanism of action of benzimidazole that does not affect the cuticles or cell membranes of the nematodes. [52,53] In addition to the red coloration of eggs treated with LdEO, in the CLSM micrographs (Figures 3 D and E) it was observed that these eggs have a higher embryonic content as a consequence of the development of the 1 st stage larvae, which could be a result of an increased size and/or change in its normal oval shape. These changes were not observed on eggs treated with 1.5 % Tween 80 (Figure 3 A-C) nor on eggs in contact with TBZ (Figure 3 G and H).…”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 97%
“…Cure rates for procaine BP-G treatments with and without neomycin have been shown to be virtually identical, (41) the same has been documented for streptomycin plus BP-G. (42) These conclusions were reached despite the fact that it was attempted that these aminoglycoside-antibacterial drugs somehow became present at the site of infection by experimental methods since normally, the concentrations they achieve in milk and/or mammary epithelium, are marginal and not useful to treat mammary infections, even those caused by gram-negative bacteria. (43) This and other arguments strongly suggest that the combined use of BP-G with an aminoglycoside does not increase the treatment efficacy over that achieved with penicillin G alone in bovine clinical mastitis caused by gram-positive bacteria sensitive to penicillin. Worldwide evidence explains why there is a worldwide tendency to revoke marketing permits for these combinations.…”
Section: Old Habits Die Hardmentioning
confidence: 92%
“…BP-G blood:tissue distribution ratio is accepted to approach 1:1, while diffusion of aminoglycosides to mammary tissue or milk is negligible. (43,44) Added to the above is the fact that there are indications that the use of aminoglycosides in human and veterinary medicine is associated with a higher prevalence of resistance in both areas, and from the perspective of "One health", it has been postulated that it is of great importance to safeguarding the clinical efficacy of aminoglycosides by rationalizing their use in human and veterinary medicine, (44) mainly because aminoglycosides have an "ɣ" phase of clearance, called residue elimination, with a half-life of 30 h or more (43,44) and therefore the potential to incur in illegal residues in products of animal origin is considerable. (45) As discussed, arguments that penicillin-streptomycin combination formulations and other combinations of β-lactams with aminoglycosides, provide synergistic efficacy in the treatment of infections in farm animals, are not well supported to date.…”
Section: Old Habits Die Hardmentioning
confidence: 99%
See 1 more Smart Citation